2011
DOI: 10.1111/j.1365-2788.2010.01367.x
|View full text |Cite
|
Sign up to set email alerts
|

Training emotional intelligence related to treatment skills of staff working with clients with intellectual disabilities and challenging behaviour

Abstract: The positive effect of the training programme on emotional intelligence is consistent with previous research on emotional intelligence and suggests that emotional intelligence of staff working with clients with ID and challenging behaviour can be influenced by training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 31 publications
2
43
0
1
Order By: Relevance
“…The training is described in detail by Zijlmans et al . (). In this study the training is described briefly.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The training is described in detail by Zijlmans et al . (). In this study the training is described briefly.…”
Section: Methodsmentioning
confidence: 97%
“…Finally, research on EI has shown that this construct is trainable (Freedman ; Zijlmans et al . ). For instance, Wasseveld et al .…”
Section: Introductionmentioning
confidence: 97%
“…; Zijlmans et al . ). EI seems to have a major protective influence on burnout (Antoniou & Koronaiou ; Beauvais et al .…”
Section: Introductionmentioning
confidence: 97%
“…Research conducted on Cognitive Behavioral Therapy (CBT) interventions with individuals living with an intellectual disability are constantly increasing and is promising [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Recently, studies have begun to demonstrate the possibilities of using group behavioral cognitive therapy for this population [19].…”
Section: Introductionmentioning
confidence: 99%